An analytical method for the resistance of cellular beams with sinusoidal openings. (15th July 2017) - Martin, P.-O.; Couchaux, M.; Vassart, O.; Bureau, A.
Highlights: A new type of cellular beams appeared recently, with sinusoidal openings A research project has been undertaken about their static behaviour This paper presents the results of tests and numerical simulations Ultimate loads and failure modes were investigated A new analytical is proposed and calibrated for the ultimate resistance. Abstract: A new type of cellular beams fabricated from hot rolled profiles appeared recently, whose openings have a sinusoidal shape. These beams are used either for steel or composite structures and they allow rectangular ducts, even with large sizes, to pass through their openings. They can thus lead to a substantial reduction of the floor thickness and they contribute to increase the competitiveness of steel buildings. The aesthetic shape of the openings is also an advantage to improve the architectural attractiveness of steel frames. To take benefit from these possibilities, accurate design methods are required and this research project has been undertaken to establish the static behaviour of these beams with sinusoidal openings. This paper presents the results of 4 tests (on 3 steel beams and on a composite beam) and of 287 numerical simulations carried out to determine ultimate loads and failure modes under the simultaneous effects of bending and shear. A new analytical design method is then proposed for the resistance of cellular beams with sinusoidal openings taking into account the Vierendel effect. This new model can be used within the range of the geometrical and mechanical scope. Finally the comparison of the ultimate loads according to this new model and according to the reference database (experimental or numerical data) is provided to assess the safety and accuracy of the proposed expressions.